How to build LEGO cars : Ideas for more than 30 models - Dolan, Hannah; Dias, Nate (New York : DK /Penguin Random House, 2021)
Presents step-by-step instructions on how to build over thiry LEGO cars.
Cover title: Go on a journey to become a better builder.
6.1.
3-6.
Keywords: LEGO toys -- Juvenile literature; Models and modelmaking -- Juvenile literature; LEGO toys; Models and modelmaking